GPCRs involved in metabolic diseases: pharmacotherapeutic development updates - Jin Cheng; Chen Hui; Xie Li; Zhou Yuan; Liu Li-li; Wu Jian (Acta Pharmacologica Sinica; Vol 45, No 7 (July 2024): Acta Pharmacologica Sinica, 2024)
G protein-coupled receptors (GPCRs) are expressed in a variety of cell types and tissues, and activation of GPCRs is involved in enormous metabolic pathways, including nutrient synthesis, transportation, storage or insulin sensitivity, etc. This review intends to summarize the regulation of metabolic homeostasis and mechanisms by a series of GPCRs, such as GPR91, GPR55, GPR119, GPR109a, GPR142, GPR40, GPR41, GPR43 and GPR120. With deep understanding of GPCR’s structure and signaling pathways, it is attempting to uncover the role of GPCRs in major metabolic diseases, including metabolic syndrome, diabetes, dyslipidemia and nonalcoholic steatohepatitis, for which the global prevalence has risen during last two decades. An extensive list of agonists and antagonists with their chemical structures in a nature of small molecular compounds for above-mentioned GPCRs is provided as pharmacologic candidates, and their preliminary data of preclinical studies are discussed. Moreover, their beneficial effects in correcting abnormalities of metabolic syndrome, diabetes and dyslipidemia are summarized when clinical trials have been undertaken. Thus, accumulating data suggest that these agonists or antagonists might become as new pharmacotherapeutic candidates for the treatment of metabolic diseases.